Structural determinants of diphenethylamines for interaction with the κ opioid receptor: Synthesis, pharmacology and molecular modeling studies. Issue 19 (1st October 2016) - Guerrieri, Elena; Bermudez, Marcel; Wolber, Gerhard; Berzetei-Gurske, Ilona P.; Schmidhammer, Helmut; Spetea, Mariana
Graphical abstract: Abstract: The κ opioid (KOP) receptor crystal structure in an inactive state offers nowadays a valuable platform for inquiry into receptor function. We describe the synthesis, pharmacological evaluation and docking calculations of KOP receptor ligands from the class of diphenethylamines using an active-like structure of the KOP receptor attained by molecular dynamics simulations. The structure–activity relationships derived from computational studies was in accordance with pharmacological activities of targeted diphenethylamines at the KOP receptor established by competition binding and G protein activation in vitro assays. Our analysis identified that agonist binding results in breaking of the Arg156-Thr273 hydrogen bond, which stabilizes the inactive receptor conformation, and a crucial hydrogen bond with His291 is formed. Compounds with a phenolic 4-hydroxy group do not form the hydrogen bond with His291, an important residue for KOP affinity and agonist activity. The size of the N-substituent hosted by the hydrophobic pocket formed by Val108, Ile316 and Tyr320 considerably influences binding and selectivity, with the n -alkyl size limit being five carbon atoms, while bulky substituents turn KOP agonists in antagonists. Thus, combination of experimental and molecular modeling strategies provides an initial framework for understanding the structural features of diphenethylamines that are essential to promote binding affinity and selectivity for the KOP receptor, and may be involved in transduction of the ligand binding event into molecular changes, ultimately leading to receptor activation.